Povezivanje podunavskoga plovnog sustava s Jadranom - Vesna Cerovac (Promet - Traffic&Transportation, 1970)
In order to take active part in the international division of labor it is highly necessary to secure linkage between the Danube navigation system and the Adriatic region. The Adriatic traffic corridor has always been exposed to rigorous international competition and unless adequate quality of services is granted it shall prove impossible for Croatia to attract the traffic from Central Europe when we already report delays regarding the construction of the Rhine-Main-Danube Canal by not having yet started the projects indispensable on the provision of linkage between the Danube navigation system and the Adriatic region.